Beneficial or detrimental activity of regulatory T cells, indoleamine 2,3-dioxygenase, and heme oxygenase-1 in the lungs is influenced by the level of virulence of Mycobacterium tuberculosis strain infection - Lozano-Ordaz, Vasti; Rodriguez-Miguez, Yadira; Ortiz-Cabrera, Angel E.; Hernandez-Bazan, Sujhey; Mata-Espinosa, Dulce; Barrios-Payan, Jorge; Saavedra, Rafael; Hernandez-Pando, Rogelio (Frontiers in Cellular and Infection Microbiology, 2023)
Tuberculosis (TB) caused by the complex Mycobacterium tuberculosis (Mtb) is the main cause of death by a single bacterial agent. Last year, TB was the second leading infectious killer after SARS-CoV-2. Nevertheless, many biological and immunological aspects of TB are not completely elucidated, such as the complex process of immunoregulation mediated by regulatory T cells (Treg cells) and the enzymes indoleamine 2,3-dioxygenase (IDO) and heme oxygenase 1 (HO-1). In this study, the contribution of these immunoregulatory factors was compared in mice infected with Mtb strains with different levels of virulence. First Balb/c mice were infected by intratracheal route, with a high dose of mild virulence reference strain H37Rv or with a highly virulent clinical isolate (strain 5186). In the lungs of infected mice, the kinetics of Treg cells during the infection were determined by cytofluorometry and the expression of IDO and HO-1 by RT-PCR and immunohistochemistry. Then, the contribution of immune-regulation mediated by Treg cells, IDO and HO-1, was evaluated by treating infected animals with specific cytotoxic monoclonal antibodies for Treg cells depletion anti-CD25 (PC61 clone) or by blocking IDO and HO-1 activity using specific inhibitors (1-methyl-D,L-tryptophan or zinc protoporphyrin-IX, respectively). Mice infected with the mild virulent strain showed a progressive increment of Treg cells, showing this highest number at the beginning of the late phase of the infection (28 days), the same trend was observed in the expression of both enzymes being macrophages the cells that showed the highest immunostaining. Animals infected with the highly virulent strain showed lower survival (34 days) and higher amounts of Treg cells, as well as higher expression of IDO and HO-1 one week before. In comparison with non-treated animals, mice infected with strain H37Rv with depletion of Treg cells or treated with the enzymes blockers during late infection showed a significant decrease of bacilli loads, higher expression of IFN-g and lower IL-4 but with a similar extension of inflammatory lung consolidation determined by automated morphometry. In contrast, the depletion of Treg cells in infected mice with the highly virulent strain 5186 produced diffuse alveolar damage that was similar to severe acute viral pneumonia, lesser survival and increase of bacillary loads, while blocking of both IDO and HO-1 produced high bacillary loads and extensive pneumonia with necrosis. Thus, it seems that Treg cells, IDO and HO-1 activities are detrimental during late pulmonary TB induced by mild virulence Mtb, probably because these factors decrease immune protection mediated by the Th1 response. In contrast, Treg cells, IDO and HO-1 are beneficial when the infection is produced by a highly virulent strain, by regulation of excessive inflammation that produced alveolar damage, pulmonary necrosis, acute respiratory insufficiency, and rapid death.